PENCIPTAAN ALAM SEMESTA PERSPEKTIF AL-QUR’AN DAN SAINS (Studi Komparatif Tafsir Al-Azhar Dan Tafsir Al-Miṣbāḥ) - Muhammad Makrus (Journal Khafi : Journal Of Islamic Studies, 2023)
The universe which has a very orderly and complex arrangement is a sign of the power of its creator. The universe in which there is earth as a place of life for humans and at the same time as a place of death for humans is created according to human needs. Some people think that the universe was created because of the role of the creator, namely God, but some think that the universe was not created by the creator. Among these thinkers was Isaac Newton of the 17th-18th centuries with the theory